Collaborative Learning Approach (CLA) in Improving Reading Proficiency - Delima, Ronnel Rey R.; Risonar, Cupid Jones O.; Digamon, Jayson S. (Future Science / FSH-PH Publications, 2024)
Studies show that Filipino learners are not demonstrating proficiency in reading. In the recent Program for International Student Assessment (PISA) 2023 results, Filipino students were found to be poor at reading proficiency. One potential strategy is collaborative learning. Thus, this study aimed to determine the effect of the Collaborative Learning Approach (CLA) on the reading proficiency of seventh-grade students. This study used a quasi-experimental design with two experimental and control groups. Using purposive sampling, two grade 7 sections of the research site were included in the study. There were 26 students in one section who were chosen to be part of the experimental group and 24 in the other section, constituting the control group, for 50 students. Each group was given a pretest and a post-test. Students in the experimental group employed the collaborative reading method, while the control group used the traditional method. The questionnaire was validated by experts and deemed reliable, scoring .70 on the Kuder-Richardson test. Mean scores and independent t-tests were used to analyze the data. Results revealed a significant difference between the experimental and control groups regarding reading proficiency after the intervention of CLA with a p-value of 0.000. It was concluded that CLA significantly influences reading proficiency and can be recommended for use in the classroom. However, based on the PHIL-IRI criteria for reading proficiency, the students in the experimental group did not meet the minimum instructional or proficiency level requirements. It is therefore suggested that further research must be done to make conclusive evidence that CLA significantly influences reading proficiency and evaluate PHIL-IRI criteria for reading proficiency, considering that it is inconsistent with the independent t-test results showing a significant difference in the reading proficiency of the experimental group.